A survey on weeds management practices among the paddy growers at Kelantan - Mohd Adib, Mohd Nafi (2015)
A weed is defined as any plant growing where it is not wanted. This definition can apply to crops, native plants as well as non-native species. However weeds are not just unwanted species but they also can have substantial negative impacts when they are present. A study on weed management practices among the growers was conducted in Kelantan Darul Naim. The main objectives of the study were to survey the weed management practices among the growers at paddy field in Kelantan. Next is to identify common weed management practices in paddy field and to identify their knowledge level, acceptance, and perception of good weed management practices. The data and information used in this study were collected by distributing questionnaires using Likert's scale in paddy field at Kelantan which are KADA areas. There are three sections in the questionnaire which are section A, knowledge level, section B, perception level and section C, acceptance level of farmers towards weeds management practices.